BS EN 14758-1. Plastics piping systems for non-pressure underground drainage and sewerage. Polypropylene with mineral modifiers (PP-MD). Part 1. Specifications for pipes, fittings and the system (23rd December 2021) - British Standards Institution,
No abstract available